Antibody and T-Cell Subsets Analysis Unveils an Immune Profile Heterogeneity Mediating Long-term Responses in Individuals Vaccinated Against SARS-CoV-2. (19th October 2022) - Agallou, Maria; Koutsoni, Olga S; Michail, Maria; Zisimopoulou, Paraskevi; Tsitsilonis, Ourania E; Karagouni, Evdokia
Abstract: Background: Based on the fact that coronavirus disease 2019 (COVID-19) is still spreading despite worldwide vaccine administration, there is an imperative need to understand the underlying mechanisms of vaccine-induced interindividual immune response variations. Methods: We compared humoral and cellular immune responses in 127 individuals vaccinated with either BNT162b2, mRNA-1273, or ChAdOx1-nCoV-19 vaccine. Results: Both mRNA vaccines induced faster and stronger humoral responses as assessed by high spike- and RBD-specific antibody titers and neutralizing efficacy in comparison to ChAdOx1-nCoV-19 vaccine. At 7 months postvaccination, a decreasing trend in humoral responses was observed, irrespective of the vaccine administered. Correlation analysis between anti-S1 IgG and interferon-γ (IFN-γ) production unveiled a heterogeneous immune profile among BNT162b2-vaccinated individuals. Specifically, vaccination in the high-responder group induced sizable populations of polyfunctional memory CD4 + helper T cells (TH 1), follicular helper T cells (TFH ), and T cells with features of stemness (TSCM ), along with high neutralizing antibody production that persisted up to 7 months. In contrast, low responders were characterized by significantly lower antibody titers and memory T cells and a considerably lower capacity for interleukin-2 and IFN-γ production. Conclusions: We identified that long-term humoral responses correlate with the individual's ability to produce antigen-specific persistent memory T-cell populations. Abstract : A longitudinal study conducted in 2021 revealed that the long-term humoral responses against SARS-CoV-2 detected among BNT162b2-vaccinated individuals correlated with individual's ability to produce persistent antigen-specific TFH and CD4 + T-cell memory populations.